PRIVATE LABEL AND RETAIL CONSUMER PERCEPTION AT SURABAYA - SUSANTI, . (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Private label is a brand owned by the retailer. Private label is expected to continue to grow to meet the needs of customers and increase margins of modern retailers. Customer is politically subdivided into different segments, the segment that focuses on brand and segment that factor giving priority to price factors. Many perceptions that emerged today that national brands have better quality than the private label. Not least dubious about the quality of Private Label Brand despite the later quality are considered equal for some product categories. Private label has an influence on the shopping preferences of customers because consumers will be sought between private label retailer with customer shopping preferences. Although private label products has become such a trend among retailers, private label penetration is the use of products in the community is still terhadang by the presence of national brands. Many perceptions that emerged today that national brands have better quality than the private label. Consumers are accustomed to buying goods with Indonesia brand nationally and the subjective attitude of pride and belief in such brands, national status, and security into consideration factors. In this respect, the attitude of consumers to the brand can change from situation of national outlets and private label products in the existing outlets.